Conformational analysis on the wild type and mutated forms of human ORF1p: a molecular dynamics study1. Issue 7 (16th July 2015) - Muthukumaran, Rajagopalan; Sangeetha, Balasubramanian; Amutha, Ramaswamy
<x xml:space="preserve">Abstract</x> Structural dynamics of human ORF1p emphasizes the role of Tyr282 in regulating ribonucleoprotein complex formation.